Straightening Identities in the Onsager Algebra - Chamberlin, Samuel Herron; Rafizadeh, Azadeh; Samsel, Matthew; Strong, Denver (The PUMP Journal of Undergraduate Research, 2019)
The purpose of this work is to formulate and prove some straightening identities in the Onsager algebra. Our identities allow one to rewrite specific products of basis elements as linear combinations of products which are in a different order. Such identities could be helpful in understanding the representation theory of the Onsager algebra.